Una revisión contemporánea a la doctrina de la distinción de poderes. (2017)
The distinction of powers is a typically modern doctrine. With it, reference is often made to the principles of division of power, separation of powers and checks and balances between the organs of political power. This doctrine is valid in our days, while it is usually based on it the structuring of states from modernity to our days. However, as a result of the challenges facing the contemporary State, this doctrine is in question, so have appeared defenders and contemporary detractors of the same. In this vein, this document offers some clarifications on the origins, scope and content of the distinction of powers by referring to its doctrinal origins.